Efektivitas Pembinaan Narapidana Narkotika dalam Pencegahan Residivisme di Sulawesi Tengah - Dinda Salfadilla; Nurhayati Mardin; Imran (Fakultas Hukum Universitas Riau, 2026)
Drug-related recidivism remains a serious concern within Indonesia's correctional system. Records from the Regional Office of the Ministry of Immigration and Corrections of Central Sulawesi for 2025 show 378 repeat offenders among 2,078 narcotics inmates, about 18 percent, amid occupancy levels nearing 95 percent above capacity. This study analyzes the effectiveness of narcotics inmates' correctional programs in preventing recidivism and identifies obstacles to their implementation. The study employs an empirical juridical approach combined with statutory and sociology-of-law approaches, drawing on 75 inmate respondents and four correctional officials at Class IIA Palu, Class IIB Toli-Toli, Class III Kolonodale, and Class III Palu Women's Prisons. The findings reveal that correctional work is delivered through personality development, independence training, narcotics rehabilitation, and social reintegration schemes covering parole, conditional leave, and pre-release leave. Environmental factors dominate initial involvement (53.33%), while nearby drug distribution networks are the leading trigger of reoffending (42.5%). Programme effectiveness is constrained by overcrowding, the absence of resident psychologists, ad hoc addiction-therapy cooperation with the National Narcotics Agency, limited facilities, weak family support, and discontinued post-release supervision. Building on these findings, the study recommends assigning permanent psychologists and addiction counsellors to every prison, adopting risk and needs assessment as the basis for individualised programmes that address environmental and network-related triggers of reoffending, and institutionalising after-care through binding cooperation agreements among prisons, the Correctional Centre, regional government, and rehabilitation agencies. Strengthening structured, individualized correctional programs and cross-institutional coordination constitutes a strategic priority for reducing narcotics recidivism in Central Sulawesi.